PERSEPSI WISATAWAN TERHADAP PEDAGANG ASONGAN DI DAYA TARIK WISATA PANTAI KUTA BALI - Roels Ni Made Sri Puspa Dewi (Jurnal Hospitality dan Pariwisata, 2021)
The purpose of this study is to determine the perceptions of tourists on hawkers at Kuta Beach, to determine the role of managers in handling hawkers at Kuta Beach, and to know the impact of hawkers on Kuta Beach Tourism Attractions. Data collection methods used were observation, interviews, questionnaires, and literature study. Respondents came from domestic tourists and foreign tourists who were visiting the Kuta Beach with 30 people respondents. Informants are taken from several hawkers who sell on Kuta Beach and the Head of Kuta Beach Tourism Object Manager. Methods of data analysis using qualitative data analysis methods assisted by a Likert scale. The calculation using the Likert Scale shows that the average result of tourists 'perceptions of hawkers at Kuta Beach Tourism Object is 3.13 which means that they are classified as Neutral, which means that tourists' perceptions of hospitality, politeness, communication, price, and product quality are neutral or sufficient. The suggestion that can be given to the Kuta Beach Tourism Object Manager is to further increase the supervision and guidance of the Kuta Beach Tourism Object management and pay more attention to the existence of hawkers. Provide coaching and training so that hospitality, courtesy, communication can be improved for the better. So that the negative impact of the hawkers can be minimized properly.